(untitled) (Journal of Philosophy Culture and Political Science, 2015)
In human history, there is an attempt attacks on national unity through the use of cultural and religious factors. In most cases, the missionary activity in Kazakhstan is held by foreign missionaries and regulated by international and domestic laws. The transnational nature of missionary activity generally increases the relevance this article on an international scale. The author analyzes the history and development of the missionary, missionary to explore the manifestations of modernity. The article defines such terms as «proselytism», «conversion». The influence of different forms missionary activity, spiritual expansion, religious ignorance on the formation of the religious consciousness of society reinforces the relevance the article. And notes the importance of missionary activity research strategies in the definition of ethno-religious and civic identity, preservation of the state integrity. Key words: missionary proselytizing, mission, Buddhism, Christianity, Islam.